Kemenangan Australia dalam Tuntutan Anggota WTO Mengenai Kebijakan Kemasan Polos pada Bungkus Rokok dan Produk Tembakau - Fahri, Muhammad Azhar; Susiatiningsih, Hermini (Journal of International Relations, 2018)
Australia's interest in improving the quality of public health by reducing the level ofsmokers through a plain packaging policy has sparked debate from the five member statesof the WTO. The lawsuit against Australia is the effort of the five member states to cancelout Australia's plain packaging policy which views the policy as violating the rules inTRIPS. The five claimant countries claiming a plain packaging policy could potentiallythreaten cigarette manufacturers with reduced market share in Australia. This researchaims to explain the efforts of the Australian Government to win the case at the WTO onthe policy of plain packaging of cigarretes and tobacco products as Australia's national lawover the accusation of the five WTO member states. This research uses realism tounderstand actors action. Technique data collection on this research using secondary datathrough literature study by processing data from books, journals, and official website. Theresults of this research explain that Australia's victory is the result of a rational choice ofbargaining position calculation based on strong Australian national interest, strong counterwinning argument at WTO trial and successful use of WHO FCTC as legal umbrella forplain packaging policy. Through the viewpoint of realism explained that conflict in thiscase based on differences interpretation of TRIPS from national interest sparked debateamong the actors involved, and the capability of actors is the key to victory in the case ofplain packaging policy.